Caracterização físico-química e química com ênfase nos compostos voláteis das polpas de açaí (Euterpe oleracea Mart.) e cupuaçu (Theobroma grandiflorum Schum.) - Oliveira, Sheila Cristina de (2011)
The study of volatile compounds responsible for fruit aroma is important for the characterization and formulation of aromas. Assai (Euterpe oleracea Mart.) and cupuassu (Theobroma grandiflorum Schum.) fruits are native to the Amazon region and its economic value lies in its pulp. The aim of this study was to determine the physicochemical characteristics as well as to identify the volatile compounds by the techniques of Solid Phase Microextraction (SPME) and Simultaneous Distillation and Extraction (DES) in assai and cupuassu pulps. The assai pulp had its acidity varying from 0.19 to 0.23%, soluble solids from 3.30 to 3.46 °Brix, pH from 4.86 to 5.02, total sugars from 3.10 to 3.57%, antioxidant activity from 1390.15 to 2110.10 gfruit/gDPPH, total phenolic compounds from 106.87 to 110.83 mg/100g. The cupuassu pulp had its acidity ranging from 1.68 to 2.06, soluble solids ranging from 11.06 to 12.83 °Brix, the pH value from 3.05 to 3.38, total sugars from 6.66 to 7.59%, L-ascorbic acid from 6.06 to 7.42 mg/100g, antioxidant activity from 4190.05 to 4640.00 gfruit/gDPPH, total phenolic compounds from 88.24 to 98.00 mg/100g. In DES of volatile extracts obtained from assai pulp, the prominent volatile compounds were 3-methyl-4-penten-1-ol (10.62%), 2-methyl-butanol (6.31%), 3-methyl-butanol (6.26%), (Z)-9-ethyl octadecenoate (5.55%), 1,2,3-trimethyl-benzene (4.37%), hexanal (3.51%), 4-methyl-2- pentanol (3.28 %), ethylbenzene (2.90%) and ethyl hexadecanoate (2.68%) while from SPME, the compounds were hexanal (34.85%), (Z) 3-hexenol (14.80%), (Z)-3-hexanol (13.40%), benzaldehyde (8.04%), linalool furanoid (3.97%), 2-methyl-but-3-en-1-ol (3.80%), isophorone (2.94%), 3-methyl-3-butenol (1.85%), myrtanol (1.36%) and hexanol (1.30%). In DES for volatile extracts obtained from the cupuassu pulp, the compounds identified were 2,4,5-trimethyl-1,3-dioxolane (14.51 %), linalool (10.26%), ethyl butyrate (7.64%), ethyl hexanoate (5.50%), 2-methyl-2-methyl-propyl propionate (4.50%), 2-methyl-1-butanol (3.48%), α-terpinol (2.65%), 3-methyl-2-pentanone (2.32%), 1,2,3-trimethyl-benzene (1.95%), and butyl butanoate (1.68%), while in SPME of cupuassu pulp, the major compounds were ethyl butyrate (16.15%), linalool (14.02%), ethyl hexanoate (11.90%), 2,4,5-trimethyl-1,3-dioxolane-trans (11.45%), 2,4,5-trimethyl-1,3-dioxolane-cis (7.71%), 3-hydroxy-ethyl-butanoate (3.26%) and 2- propenyl-butanoate (3.21%). The technique of solid microextraction (SPME) yielded better results for the extraction and separation of assai and cupuassu pulps, presentend increased quantification of major volatile compounds identified in the pulps.